2022
DOI: 10.3389/fsufs.2022.838824
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Drought and Its Potential Impacts: Enabling Decision-Support for Food Security in Vulnerable Regions

Abstract: Increasing demand for food and environmental stressors are some of the most challenging problems that human societies face today and these have encouraged new studies to examine drought impacts on food production. Seeking to discuss these important issues in the South African context, this study analyzed the impacts of drought on food security in one of the country's largest commercial agricultural land (Free State Province). Earth observation and crop data were acquired from Application for Extracting and Exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 54 publications
(71 reference statements)
0
23
0
Order By: Relevance
“…Agricultural droughts' effects on food supplies may be measured, allowing governments to make more sustainable policies. It needs a comprehensive assessment of the links between spatiotemporal drought variations, farming systems, irrigation impacts, and the available water resources [16]. Drought-prone locations have a wide multitude of issues in terms of intensity, spatial and temporal scales.…”
Section: Drought Is Further Classified Into Different Categories: I) ...mentioning
confidence: 99%
“…Agricultural droughts' effects on food supplies may be measured, allowing governments to make more sustainable policies. It needs a comprehensive assessment of the links between spatiotemporal drought variations, farming systems, irrigation impacts, and the available water resources [16]. Drought-prone locations have a wide multitude of issues in terms of intensity, spatial and temporal scales.…”
Section: Drought Is Further Classified Into Different Categories: I) ...mentioning
confidence: 99%
“…Drought is one of the most serious natural disasters, with high frequency, long duration, and range-wide impact [1]. Against the background of climate change, the impact of drought on agriculture, the economy, and society has intensified in recent decades [2][3][4][5]. It is reported that the annual economic losses caused by drought worldwide are as high as USD 6-8 billion, far exceeding other meteorological disasters [6].…”
Section: Introductionmentioning
confidence: 99%
“…These stressors greatly limit the distribution of plants, alter growth/development patterns, and reduce seed yield [ 4 ]. Studying drought and its potential impacts on food security is crucial in a global context [ 5 ]. Drought induces oxidative stress through the overproduction of reactive-oxygen species (ROS), ultimately causing the cell membrane to rupture and stimulating various stress-signaling pathways, including ROS, mitogen-activated protein kinase, Ca 2+ , and hormone-mediated signaling.…”
Section: Introductionmentioning
confidence: 99%